Buyer-supplier collaboration : a sensemaking perspective - Lombard, Marion Fiona (Trinity College (Dublin, Ireland). Trinity Business School, 2009)
This thesis provides an empirical investigation of how buyer and supplier teams make sense of collaboration. Specifically, this thesis explores how buyer and supplier parties interpret collaboration and how their interpretations of collaboration evolve over time. In addition, it considers the actions that accompany buyer and supplier parties’ interpretations of collaboration and how these actions link to interpretations. Taking a sensemaking making perspective, this thesis considers collaboration as an interpretative process. The forces which mediate the interpretations of collaboration in this buyer and supplier context are also explored. Consistent with the interpretivist approach underpinning this thesis, a process approach is adopted, using a qualitative multiple case study design. A comparative cross-case analysis of four buyer and four supplier teams is undertaken to address the research questions in this study.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin